Optical Imaging Visualizes a Homogeneous and Horizontal Band-Like Biodistribution of Large- and Small-Size Hydrophilic Compounds Delivered by Ablative Fractional Laser - Rikke Louise Christensen; Vinzent Kevin Ortner; Merete Haedersdal; Uffe Høgh Olesen (MDPI AG, 2022)
The skin barrier generally limits the topical delivery of hydrophilic molecules. Ablative fractional laser (AFL) facilitates cutaneous drug uptake of smaller hydrophilic compounds in several studies. In this imaging-based study, we aim to investigate the cutaneous biodistribution of two different-sized hydrophilic compounds delivered by an ablative fractional CO2 laser at minimally invasive settings. Intact or CO2 AFL-pretreated (2.5 mJ/mb and 5% density) ex vivo porcine skin was topically applied with a large or small hydrophilic compound (fluorescence labeled antibody nivolumab (150,000 g/mol, n = 4) or ATTO 647N (746 g/mol, n = 3)). Samples were incubated for 20 h in a Franz cell setup, whereafter optical coherence tomography (OCT) was used to assess laser channel depth, and ex vivo confocal microscopy (EVCM) was used to assess epidermal thickness and cutaneous biodistribution of nivolumab and ATTO 647N. With an EVCM-assessed median epidermal thickness of 70.3 µm and OCT-assessed ablation depth of 31.9 µm, minimally invasive settings enabled shallow penetration into the mid-epidermis. The AFL-assisted uptake of the antibody nivolumab and the smaller compound ATTO 647N showed a similar homogenous and horizontal band-like biodistribution pattern that reached mid-dermis. No uptake of nivolumab or ATTO 647N was observed in intact skin. In conclusion, AFL-induced mid-epidermal laser channels facilitates the cutaneous delivery of two hydrophilic compounds that are distributed in a similar homogeneous and horizontal band-like pattern, irrespective of their molecular size.